(untitled) (Canadian Hematology Today, 2022)
Waldenström Macroglobulinemia (WM) is a mature B-cell neoplasm categorized as a lymphoplasmacytic lymphoma (LPL) with monoclonal immunoglobulin M (IgM) production. WM comprises a spectrum of clinical manifestations related to (a) excessive infiltration of the bone marrow and/or other organs (lymph nodes, spleen, extranodal organs) by the LPL infiltrate, and (b) the impact of excess IgM on the circulatory and immune systems, and end organs. The latter includes serum hyperviscosity, infection related to suppression of other immunoglobulins, autoimmune cytopenias, cryoglobulinemia, production of anti-myelin-associated glycoprotein antibodies leading to peripheral neuropathy, and occasionally AL amyloidosis with end-organ deposition.